NiCo2O4@Ni2P nanorods grown on nickel nanorod arrays as a bifunctional catalyst for efficient overall water splitting. (September 2020) - Wang, Q.; Wang, H.; Cheng, X.; Fritz, M.; Wang, D.; Li, H.; Bund, A.; Chen, G.; Schaaf, P.
Abstract: The development of efficient and durable non-noble metal catalysts remains a challenge in electrocatalytic water splitting applications. To address this, a bifunctional catalyst involving hierarchical NiCo2 O4 @Ni2 P nanorods grown on nickel nanorod arrays (NiCo2 O4 @Ni2 P/NAs) was designed and fabricated in this study for overall water splitting that provided high activity and acceptable stability. And if used as the cathode and anode in alkaline media, the NiCo2 O4 @Ni2 P/NAs only required 1.58 V to achieve a current density of 10 mA cm −2, which is superior to most reported catalysts and can be attributed to a unique core-shell structure and coexisting crystalline/amorphous Ni2 P phases. Graphical abstract: Image 1 Highlights: Hierarchical NiCo2 O4 @Ni2 P nanorods grown on nickel nanorod arrays. Hierarchical structured improve charge/mass transfer abilities. Co-existing crystalline/amorphous Ni2 P phases providing increased interfaces as active sites. A lower cell voltage of 1.58 V to reach a current density 10 mA cm −2 for overall water splitting.